Proceedings of the 35th IEEE/ACM International Conference on Automated Software Engineering 2020
DOI: 10.1145/3324884.3416540
|View full text |Cite
|
Sign up to set email alerts
|

Automated implementation of windows-related security-configuration guides

Abstract: Hardening is the process of configuring IT systems to ensure the security of the systems' components and data they process or store. The complexity of contemporary IT infrastructures, however, renders manual security hardening and maintenance a daunting task.In many organizations, security-configuration guides expressed in the SCAP (Security Content Automation Protocol) are used as a basis for hardening, but these guides by themselves provide no means for automatically implementing the required configurations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Adding machine-readable information from which implementations and checks can be derived requires, of course, manual effort, but such effort would be necessary for generating separate implementation mechanism, as well. Furthermore, for some use-cases, semi-automated mechanisms for deriving machine-readable information from humanreadable text exist [26]. guides.…”
Section: Contributionsmentioning
confidence: 99%
“…Adding machine-readable information from which implementations and checks can be derived requires, of course, manual effort, but such effort would be necessary for generating separate implementation mechanism, as well. Furthermore, for some use-cases, semi-automated mechanisms for deriving machine-readable information from humanreadable text exist [26]. guides.…”
Section: Contributionsmentioning
confidence: 99%
“…Research about configuration is an essential part of the software engineering [1,6] as well as the security domain [4,10]. Stöckle et al demonstrated how one could use NLP to implement guides efficiently [9]. Most relevant for the problem of identifying sr settings is sentiment analysis, where we classify documents as being positive or negative, depending on the expressed sentiment [5].…”
Section: Related Workmentioning
confidence: 99%